Finders keepers a tale of archaeological plunder and obsession - Childs, Craig 1967- (Little, Brown and Co., 2010)
Beyond what most people think about archaeology--with its cleanly numbered dates, and discoveries--lies a vibrant and controversial realm of scientists, thieves, and contested land claims. Here, naturalist and adventurer Childs explores the field?s transgressions against the cultures it tries to preserve, and pauses to ask: To whom does the past belong? Written in his trademark lyrical style, this book carries readers directly into his adventures and discoveries, lifting the curtain on the ethical dilemmas and dark side of archaeology. It is a book about man and nature, remnants and memory, a dashing tale of crime and detection--in other words, a ghost story.--From publisher description.